Interface-induced superconductivity and strain-dependent spin density waves in FeSe/SrTiO3 thin films - Tan, Shiyong; Zhang, Yan; Xia, Miao; Ye, Zirong; Chen, Fei; Xie, Xin; Peng, Rui; Xu, Difei; Fan, Qin; Xu, Haichao; Jiang, Juan; Zhang, Tong; et al. (Nature materials, 2013)
The record superconducting transition temperature ( T c ) for the iron-based high-temperature superconductors (Fe-HTS) has long been 56 K. Recently, in single-layer FeSe films grown on SrTiO 3 substrates, indications of a new record of 65 K have been reported. Using in situ photoemission measurements, we substantiate the presence of spin density waves (SDWs) in FeSe films—a key ingredient of Fe-HTS that was missed in FeSe before—and we find that this weakens with increased thickness or reduced strain. We demonstrate that the superconductivity occurs when the electrons transferred from the oxygen-vacant substrate suppress the otherwise pronounced SDWs in single-layer FeSe. Beyond providing a comprehensive understanding of FeSe films and directions to further enhance its T c , we map out the phase diagram of FeSe as a function of lattice constant, which contains all the essential physics of Fe-HTS. With the simplest structure, cleanest composition and single tuning parameter, monolayer FeSe is an ideal system for testing theories of Fe-HTS. Iron pnictide superconductors represent a suggestive alternative to cuprate superconductors for achieving high transition temperatures. Using in situ angle-resolved photoemission spectroscopy, the electronic properties of FeSe are examined as a function of film thickness, providing valuable insights into the mechanism driving the superconductivity in this material.